2011
DOI: 10.1016/j.taap.2011.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of carbon nanofibers: Are they potentially more or less dangerous than carbon nanotubes or asbestos?

Abstract: The production of carbon nanofibers and nanotubes (CNF/CNT) and their composite products is increasing globally. CNF are generating great interest in industrial sectors such as energy production and electronics, where alternative materials may have limited performance or are produced at a much higher cost. However, despite the increasing industrial use of carbon nanofibers, information on their potential adverse health effects is limited. In the current study, we examine the cytotoxic and genotoxic potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 59 publications
7
110
0
2
Order By: Relevance
“…37,38 Purified CNTs have been reported to generate low levels of reactive species in a cellular system yet remain bioactive in vivo. 16,39 Low doses of SWCNTs, representative of CNT lung burdens and alveolar epithelial cell surface area achieved after aspiration of 40 μg/mouse, exhibit low cytotoxicity. Rather, low dose SWCNT exposure of lung fibroblasts increases proliferation rate and collagen production.…”
Section: In Vitro Responses To Cntsmentioning
confidence: 99%
See 2 more Smart Citations
“…37,38 Purified CNTs have been reported to generate low levels of reactive species in a cellular system yet remain bioactive in vivo. 16,39 Low doses of SWCNTs, representative of CNT lung burdens and alveolar epithelial cell surface area achieved after aspiration of 40 μg/mouse, exhibit low cytotoxicity. Rather, low dose SWCNT exposure of lung fibroblasts increases proliferation rate and collagen production.…”
Section: In Vitro Responses To Cntsmentioning
confidence: 99%
“…41,42 Purified SWCNTs do not generate radicals yet cause a measurable level of genotoxicity to fibroblasts in the comet and micronucleus assay. 39 However, CNFs generate significant radicals and are more genotoxic than SWCNTs. 43 Sargent et al 44 reported that SWCNTs disrupt centrosomes in dividing lung epithelial cells resulting in multipolar mitosis and aneuploidy.…”
Section: In Vitro Responses To Cntsmentioning
confidence: 99%
See 1 more Smart Citation
“…: TGA, EELS e microscopia de alta resolução). 114,118 Entre os vários trabalhos de genotoxicidade publicados 75,85,94,[121][122][123][124] poucos têm feito uso de análises térmicas (um parâmetro importante para caracterização e recomendado pelo National Institute of Standards and Technology). Muitos trabalhos apresentam imagens de microscopia, porém essas são de baixa resolução 74,83,85,87,88,93,97 o que compromete o entendimento dos tipos de contaminantes existentes nos NTCs.…”
Section: Considerações Finaisunclassified
“…Furthermore, among the few studies that have evaluated CNF toxicity, only in vitro-cultured cell models have been used. 7,10,11 Although nanomaterial-mediated toxicity has been largely attributed to the generation of free radicals, the exact molecular mechanism underlying reactive oxygen species (ROS) generation by nanoparticles remains unclear. [12][13][14] Flies exposed to silver nanoparticles are known to show depleted levels of glutathione (GSH) as well as increased antioxidant enzyme SOD and CAT activities.…”
Section: Introductionmentioning
confidence: 99%